Culinary MSMEs Accounting System Design: “Pempek Lin Friends Palembang” - Erlyna Juany; Meiliana Suparman (Institut Teknologi Nasional, Bandung, 2023)
The majority of MSMEs in Indonesia are lack of adequate accounting records. Therefore, it is difficult to estimate the volume of their financial transactions and develop their business. The objective of this community service project is to provide a tailored accounting system for